What Drives the Volatility of Firm Level Productivity in China? - Luo, Xubei; Zhu, Nong (World Bank, Washington, DC, 2014)
The enterprise reforms of the 1990s profoundly changed the structure of the economy in China. With the deepening of market economy, the share of the state-owned and collective enterprises declined. Expansion and contraction, as well as establishment and closure, of firms became a common phenomenon. The level and volatility of firm productivity have become increasingly important aspects of the micro performance of the economy. This paper uses a firm-level data set collected annually by the National Bureau of Statistics of China in 1998-2007 to examine the role of different firm characteristics in productivity volatility. The paper measures productivity volatility at the firm level as the standard deviation of the annual growth rate of productivity. The main objectives are twofold: first, it examines the variation of productivity volatility across firms of different characteristics and their evolution over time; second, it investigates the sources of productivity volatility at the firm level in China. The results suggest that in general, productivity volatility at the firm level has declined over time in China. Among firms with different characteristics, large firms, old firms, foreign firms, and firms located in the coastal provinces are less volatile. Firm size and location are the two major factors that drive changes in productivity volatility, one in a positive way and one in a negative way. Although the gaps of volatility between smaller firms and larger firms declined, the gaps between firms located in the coastal provinces and inland provinces increased.